2003
DOI: 10.2223/jped.1026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preterm infant position on weaning from mechanical ventilation

Abstract: Objective: the purpose of this study was to determine the effects of prone positioning on cardiorespiratory stability and weaning outcome of preterm infants during weaning from mechanical ventilation.Methods: from January to December 1999, a sample of 42 preterm infants, with birthweight < 2,000 g, mechanically ventilated in the first week of life, were randomly divided, in the beginning of the weaning process, in two groups according to the position: supine position (n = 21) or prone position (n = 21). Heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 8 publications
2
32
0
3
Order By: Relevance
“…1 Changing a patient's posture may not seem a dramatic technique, but this simple action often prevents recourse to more time consuming or tiring techniques. Positioning should be an integral part of all respiratory care, especially when prophylaxis is the aim.…”
Section: Introductionmentioning
confidence: 99%
“…1 Changing a patient's posture may not seem a dramatic technique, but this simple action often prevents recourse to more time consuming or tiring techniques. Positioning should be an integral part of all respiratory care, especially when prophylaxis is the aim.…”
Section: Introductionmentioning
confidence: 99%
“…Nos casos em que se objetiva a remoção de secreção do trato respiratório inferior, podem ser empregadas técnicas de higiene brônquica, como a vibração, a drenagem postural e a aspiração. A ênfase é direcionada às técnicas passivas e/ou de posicionamento para preservar a estrutura respiratória, evitando ou minimizando a dor e a manipulação excessiva (19)(20)(21)(22)(23) . A técnica de vibração auxilia na mudança das características da secreção, facilitando a sua remoção (23,24) .…”
Section: Introductionunclassified
“…Antunes et al in a study on 42 ventilator dependent premature neonates revealed that prone position results in successful and faster weaning from mechanical ventilation and reduces reintubation probability [13].…”
Section: Discussionmentioning
confidence: 99%